2017
DOI: 10.1371/journal.pone.0180508
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of prevention, cause, symptom and practices of malaria among women in Burkina Faso

Abstract: BackgroundMalaria remains a major public health issue in most southern African countries as the disease remains hyper endemic. Burkina Faso continues to face challenges in the treatment of malaria, as the utilization of preventive measures remains low on a national scale. While it has been acknowledged that understanding women’s health-seeking behaviours, perception of malaria and its preventive measures will aid in the control of malaria, there is paucity of information on Knowledge, Attitudes and Practices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
48
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 31 publications
17
48
2
2
Order By: Relevance
“…Mosquito bite has been identified as the principal malaria transmission as shown in some studies in Africa, Asia and America [26][27][28][29][30][31][32][33][34][35][36]. However, our results were in contrast with those previously reported from Nigeria, where a small proportion of respondents correctly know the main malaria transmission route and its cause [37].…”
Section: Knowledge About Malariacontrasting
confidence: 99%
“…Mosquito bite has been identified as the principal malaria transmission as shown in some studies in Africa, Asia and America [26][27][28][29][30][31][32][33][34][35][36]. However, our results were in contrast with those previously reported from Nigeria, where a small proportion of respondents correctly know the main malaria transmission route and its cause [37].…”
Section: Knowledge About Malariacontrasting
confidence: 99%
“…The current study showed that educational status was an important variable which was signi cantly associated with knowledge on malaria among women of reproductive age. The nding of this study are in line with the studies that were conducted in Nigeria [13], Burkina Faso [24] and Ghana [33]. An explanation of this association may be due to the fact that educated mothers may not have problems reading and comprehending information concerning malaria.…”
Section: Discussionsupporting
confidence: 89%
“…Based on insights from relevant literature [23,24], the following independent were treated appropriate for analysis: women's age in years (15-19, 20-24, 25-29, 30-34, 35-39, 45-49); educational attainment (no formal education, primary, secondary and higher education); household has radio (no, yes); household has television (no, yes); gender of household head (male, female); wealth index (poorest/poorer/middle, richer, richest); seen/heard malaria message (no, yes); ethnicity (Chewa, Tumbuka, Lomwe, Yao, Ngoni, other); place of residence (urban, rural); and, geographical region (northern, central, southern). The wealth index is a composite measure of a household's cumulative living standard.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquito bite has been identified as the principal malaria transmission as shown in some studies in Ethiopia and elsewhere in Africa [11,13,29,[31][32]. In Ethiopia, regular practice of awareness creation in the communities about health issues through health extension workers and mass media has brought remarkable behavioral change in the control and prevention of communicable diseases.…”
Section: Discussionmentioning
confidence: 99%